1998
DOI: 10.1021/jp972575x
|View full text |Cite
|
Sign up to set email alerts
|

How To Concentrate an Aqueous Polyelectrolyte/Surfactant Mixture by Adding Water

Abstract: Aqueous systems containing sodium polyacrylate (NaPA) and the surfactant cetyltrimethylammonium bromide (CTABr) can separate into a concentrated phase and a dilute phase. The phase separation can be induced by addition of water. Further addition of water causes the concentrated phase to become still more concentrated. A structural analysis of the concentrated phase shows that the surfactant ions (CTA+) are always aggregated into elongated micelles. These micelles are packed with short-range order (concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
213
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(229 citation statements)
references
References 19 publications
14
213
0
2
Order By: Relevance
“…Lindman et al further proved that salts having the larger ionic radius like Br − would be more effective to prevent the combination of DNA and cationic surfactants than those with smaller anionic radius like Cl − [33]. This behavior could be well explained by the works of Ilekti et al and Hansson et al [34][35][36]. They concluded that there exists a clear electrostatic competition between polyions and the counterions for the association with the cationic surfactant aggregates.…”
Section: Discussionmentioning
confidence: 98%
“…Lindman et al further proved that salts having the larger ionic radius like Br − would be more effective to prevent the combination of DNA and cationic surfactants than those with smaller anionic radius like Cl − [33]. This behavior could be well explained by the works of Ilekti et al and Hansson et al [34][35][36]. They concluded that there exists a clear electrostatic competition between polyions and the counterions for the association with the cationic surfactant aggregates.…”
Section: Discussionmentioning
confidence: 98%
“…The surfactant molecules are in an aggregated form in the concentrated phase, but different types of aggregates are formed in different systems; micelles of different shape, cubic liquid crystalline phase, (normal or inverse) hexagonal phase and lamellar phase are the cases described so far (2)(3)(4)(5)(6)(7)(8)(9). The factors determining the type of aggregate formed can be assumed to be the same as for simple surfactant systems, a statement supported by some recent reports (8).…”
Section: Dna Displays a Strong Associative Behavior With Cationic Surmentioning
confidence: 99%
“…Depending on the balance between the polar and nonpolar parts, a large number of self-assembly structures is (43)(44)(45). Only recently have we started to learn about how polymers modify surfactant self-assembly structures (2,3,9,46). The first studies probing the surfactant aggregates in the concentrated phase in a phase separated polyion-surfactant system revealed by fluorescence that the aggregates are discrete and have low aggregation numbers; they are small globular, closely spherical micelles (47)(48)(49)(50).…”
Section: The Structure Of Dna-surfactant Complexes Is Importantmentioning
confidence: 99%
“…When an ion-containing polymer solution is mixed to a dispersion of oppositely charged colloids, a phase separation usually follows [13][14][15][16][17][18][19][20][21][22][23] . At the mixing, the solution becomes turbid, and after centrifugation it displays two separated phases.…”
Section: -Introductionmentioning
confidence: 99%
“…In biophysics, comprehensive studies have been dedicated to the cooperative condensation of DNA with multivalent counterions [3][4][5] or with cationic liposomes 1,[6][7][8][9] . In material science, electrostatic layer-by-layer deposition yielding polyelectrolyte multilayers have been achieved for encapsulation purposes and colloidal stabilization [10][11][12] .When an ion-containing polymer solution is mixed to a dispersion of oppositely charged colloids, a phase separation usually follows [13][14][15][16][17][18][19][20][21][22][23] . At the mixing, the solution becomes turbid, and after centrifugation it displays two separated phases.…”
mentioning
confidence: 99%